ANALISIS PEMBENTUKAN KEMENTERIAN NEGARA DALAM SISTEM PRESIDENSIAL (SUATU KAJIAN MENURUT UU NO.39 TAHUN 2008 TENTANG KEMENTRIAN NEGARA) - Hardianto, Hardianto (IAIN Palopo, 2017)
This study aims to : ( 1 ) To determine the dismissal and replacement of ministers in the Presidential system of government under Law No. 39 Year 2008 on State ministries . ( 2 ) To find out more in depth ministerial accountability in a presidential system according to the Law No. 39 Year 2008 on State ministries .This study used a normative approach that emphasizes on the research literature . Types and sources of data are the materials used in this study of primary legal materials , legal materials and secondary legal materials tersier. Teknik dipergunakan data collection in this research is the study of literature or studies document that is used to collect the data sekunder. Dalam implementation research keputustakaan documents or studies conducted on primary legal materials or data . In analyzing the data , the data have been obtained was analyzed using qualitative analysis is non- statistical data analysis .The results of this study is about the appointment and dismissal of ministers according to Law Number 39 Year 2008 on State ministry in a presidential system , majority of cabinet seats will be divided by political party supporters , so the big chair in the cabinet for supporting a political party at will , resulting in the fit and propes test in selecting candidates for ministerial ultimately not be realized in accordance with the rules and Regulations persiden as head of government is certainly expected to make good decisions in lifting the minister . But the fact that a lot of ministers who occupy a position incompatible with kompoten his knowledge and skills that impact the performance of the ineffectiveness of a state ministry .This research recommendation is for the creation of good government in the presidential system of government according to Law No. 39 of 2008 should be based on the fit and proper test and not based on political pressure in menganggkat and dismiss ministers . As well as the accountability of ministers to the president is always transparent .